2020
DOI: 10.5812/ijcm.96851
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Problems in Boys with Acute Myeloid Leukemia (AML) with Central Nervous System (CNS) Involvement; A Descriptive Study

Abstract: Background: Children with acute myeloid leukemia (AML) experience some limitations and complications because of their illness and treatment process from the onset of the diagnosis. They are also prone to some psychological problems. In previous studies, cognitive impairments were considered more than emotional and behavioral dysfunction. Objectives: This study aims at determining the impact of AML on the emotional/behavioral problems and executive functions of children compared to their healthy peers. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
(29 reference statements)
1
0
0
Order By: Relevance
“…These symptoms can lead to limit their ability to engage in normal activities such as attending school. The results of the current study agrees with new study that was stated that no significant association was found between sociodemographic characterize of acute lymphoblastic leukemia children and their psychological impact [16] .…”
Section: Discussion Of the Association Between Psychological Impact Of Chemotherapy Upon School Age Children And Their Socio-demographic supporting
confidence: 92%
“…These symptoms can lead to limit their ability to engage in normal activities such as attending school. The results of the current study agrees with new study that was stated that no significant association was found between sociodemographic characterize of acute lymphoblastic leukemia children and their psychological impact [16] .…”
Section: Discussion Of the Association Between Psychological Impact Of Chemotherapy Upon School Age Children And Their Socio-demographic supporting
confidence: 92%